PENYEBAB KEKALAHAN UMAT MUSLIM DALAM PERANG UHUD TAHUN 625 M - Dunggio, Rahmat (Historia Islamica: Journal of Islamic History and Civilization, 2022)
This article examines the history of the Uhud war which took place in 3 H/625 AD. In this war the Muslims suffered their first defeat in battle, previously the Muslims won the battle of Badr. In this article the author uses the historical method which consists of four stages, namely heuristics or data collection, the second is source criticism, the third is interpreting data, and the last is historiography or historical writing. The results of this study found three main causes of the defeat of Muslims in the Uhud war. The first cause of the change in the motivation for war which was originally to protect the Islamic religion but turned into a motivation to enrich oneself with spoils of war, besides that the second cause was the lack of discipline in the ranks of the Muslims, and the last cause was the presence of intruders in the ranks of the Muslims at that time.